Relationship between Nursing Students Motivation Level and Academic Achievement Based on Self Determination Theory - Leila Jannesar Hoseinie; Rabiallah Farmanbar; Majid Pourshaikhian; Ehsan kazemnejad Leili (Golestan University of Medical Sciences, 2014)
Background and Objective: Learning and academic achievement are the most important subjects in educational psychology influenced by some individual and situational factors. Because of lack of studied research, there is not accurate statistic about nursing students' motivation and its relation with academic achievement. Thus, we aimed to determine the relationship between nursing students' motivation and academic achievement in Guilan University of medical sciences. Material and Methods: This correlational study was conducted on 243 nursing students. Using Academic motivateion and work environment scales, data was collected and analyzed by SPSS. Results: Out of 243 participants , with the mean age of 21, 126 (51.9%) were female and 117 (48.1%) were male. student's motivation level and their grad point average (GPA) was good. There was significant positive correlation between GPA and identified motivation (p=0.03), and introjected motivation (p= 0.00). While between GPA and demotivation, the correlation was significantly negative. Extrinsic and intrinsic motivation was not correlated significantly with GPA. Conclusion: According to the study, motivation level of nursing students is high. Internal motivation is not correlated with academic achievement, but identified and introjected motivations that are in lower level in proportion to internal motivation are highly correlated. Thus, the lecturers may need to consider more attempts regarding to identifying the impressive factors affected on motivation and academic achievement, and improving intrinsic motivation.